Can We Reach a Consensus on the Appropriate Use of Before and After Photos in Breast Surgery?. Issue 7 (16th July 2021) - Valiquette, Chantal R.; Forrest, Christopher R.; Kasrai, Leila; Wanzel, Kyle R.; Martou, Glykeria; Beber, Brett A.; Semple, John L.; Constantine, Thomas; Ho, Emily S.; Somogyi, Ron B.
Abstract : Background: Breast surgery is an area of practice where patients value before and after photographs (BAPs). Consensus is needed to develop guidelines to address the deficit in the literature regarding appropriate use of BAPs, as these may ultimately play a significant role in the breast surgery consent process. Methods: Expert breast reconstructive surgeons participated in a modified nominal group technique (NGT) to establish expert consensus on categories and criteria to be used when evaluating appropriate use of BAPs as part of informed consent. Endorsement rate of 75% and coefficients of variance within and between rounds were conducted to determine validity of each criteria item's rank order. Results: Eight experts participated in the NGT in-person meeting and subsequent online survey. five of seven categories were endorsed for discussion: purpose, image type, anatomy, results, and photographic integrity. Overall consensus was obtained for six of 11 criteria. Criteria items found to have consensus were: patients considering surgery being the intended photograph audience (100% endorsement, CV1 – CV2 = 0.01), use of photographic images (75% endorsement, CV1 – CV2 = 0.04), defining the standard clinical photograph by having patients in the same body position (100% endorsement, CV1 – CV2 = 0.14), anonymizing images by removing all digital tags (88% endorsement, CV1 – CV2 = 0.03) and patient identifiers (75% endorsement, CV1 – CV2 = 0.00), not limiting the number of photograph sets needed for sufficient representation (100% endorsement, CV1 – CV2 = 0.07), and representing average outcomes (100%, CV1 – CV2 = 0.06). Conclusions: Early use of this validated and effective technique helps identify potential consensus categories and criteria that surgeons recommend for the use of BAPs in the informed consent process. Further study is required.